Comparative analysis of the general physical fitness of qualified polyathlonists - Martirosova, T. A.; Kondrashova, E. D.; Gorbachev, A. S.; Maleev, P. A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify differences in the indicators of physical fitness of polyathletes of the 1st sports category and masters of sports and to evaluate their impact on sports results.